TRANSFORMING CONSUMER EXPERIENCE THROUGH THE APPLICATION OF AUGMENTED OPTIMIZATION MARKETING IN RETAIL MARKETING STRATEGY - Suryawijaya, Tito Wira Eka; Aqmala, Diana (Strategic Management Business Journal, 2023)
This research endeavors to delve into the multifaceted role of Augmented Reality (AR) as a pivotal marketing tool within the evolving landscape of the retail sector in the aftermath of the pandemic. The research methodology adopted encompasses a quantitative approach, employing the robust Structural Equation Modeling (SEM) - Partial Least Squares (PLS) model. The process of data acquisition unfolded through a meticulously crafted online survey utilizing a Google Form-based questionnaire. The survey garnered responses from a diverse sample of 100 individuals who had actively engaged with AR features in their retail product purchases on at least two occasions. The research findings cast a spotlight on the considerable potential that AR holds in not only augmenting customer satisfaction but also in wielding influence over consumer purchasing behavior within the context of the post-pandemic retail sector. The implications drawn from these findings are transformative, suggesting that retail entities possess the capacity to strategically optimize AR technology as a dynamic and effective marketing tool. This optimization, in turn, stands poised to elevate consumer experiences, amplify levels of customer satisfaction, and catalyze the overall growth trajectory of businesses operating within the retail sector. The study introduces the concept of "Augmented Optimization Marketing," providing a nuanced perspective on the strategic utilization of AR in enhancing marketing endeavors. In essence, this research paints a comprehensive panorama of the strategic significance of AR in shaping the future landscape of retail marketing. JEL Classification: D12, M31, C83, L81, O33